05 Actualization of continuity in labor education of children of preschool and primary school age: Ukrainian context (1890- 1917) - Eugen Antypin (Association of Social and Educational Innovation, 2016)
Integration of education of Ukraine into the European educational space actualizes the problem of studying educational theory and practice to develop productive ideas that can be adapted to the content and methodical support, training and education of the individual. In historical and pedagogical context of the late XIX - early XX century are significant achievements of european and ukrainian teachers with problems of labor education of preschool and primary school age children. That is why the continuity actualized on this phenomenon. The purpose of this research is in the studying details of continuity in labor education of children; interpreting the achievements of teachers in this chronological period; the discovery of new knowledge that will expand the range of historical and pedagogical science. Results of historical and pedagogical research will help to identify those ideas that are interesting for modern education. Methodology of the research is based on studying approaches to periodization: interdisciplinarity historical and pedagogical research as a principle of periodization (H.Ivanyuk); methodological approaches to periodization of historical and educational events (Ya.Kalakura, N.Hupan, N.Dichek). To specify the period we have defined the criterion of socio-economic conditionality ideas of continuity in labor education of preschool and primary school age children. It was found that period of actualization of continuity in labor education of children in Ukraine (1890-1917) characterized by public request for workers capable of various types of work as economic development exacerbated the problem. In educational practice actively spread ideas of Y.Pestalotstsi, F.Frebel, M.Montessori about personal development of preschool, work as content, method and form of education, training children to school in kindergarten, refuge, shelters. The purpose of labor education of children is to prepare children for life and work. These ideas are relevant in the modern Ukrainian educational space.